2015
DOI: 10.1155/2015/762426
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunogenicity in Rabbits of the Polypeptides Encoded by the 5′ Terminus of Hepatitis C Virus RNA

Abstract: Recent studies on the primate protection from HCV infection stressed the importance of immune response against structural viral proteins. Strong immune response against nucleocapsid (core) protein was difficult to achieve, requesting further experimentation in large animals. Here, we analyzed the immunogenicity of core aa 1–173, 1–152, and 147–191 and of its main alternative reading frame product F-protein in rabbits. Core aa 147–191 was synthesized; other polypeptides were obtained by expression in E. coli. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…In Series I, we assessed the immunogenicity of the expression optimized HCV Core152opt. Splenocytes collected by the experimental endpoint were assessed for the capacity to produce IFN-γ, IL-2 and TNF-α alone and in combination in response to stimulation with pool of peptides encompassing aa 61-175 of HCV core ( Supplementary Table S1 ) recognized in mice [ 36 , 48 ]. In Core152opt DNA-immunized mice, we registered potent response characterized by secretion of IL-2, dual secretion of IFN-γ/TNF-α and triple secretion of IFN-γ/ IL-2/TNF-α by CD4+ T cells, while Core191v immunized mice responded by only by production of IFN-γ ( Figure 2 A,C).…”
Section: Resultsmentioning
confidence: 99%
“…In Series I, we assessed the immunogenicity of the expression optimized HCV Core152opt. Splenocytes collected by the experimental endpoint were assessed for the capacity to produce IFN-γ, IL-2 and TNF-α alone and in combination in response to stimulation with pool of peptides encompassing aa 61-175 of HCV core ( Supplementary Table S1 ) recognized in mice [ 36 , 48 ]. In Core152opt DNA-immunized mice, we registered potent response characterized by secretion of IL-2, dual secretion of IFN-γ/TNF-α and triple secretion of IFN-γ/ IL-2/TNF-α by CD4+ T cells, while Core191v immunized mice responded by only by production of IFN-γ ( Figure 2 A,C).…”
Section: Resultsmentioning
confidence: 99%
“…Repeated attempts to induce potent anti-core immune response met with difficulties, even when using viral vectors [5,6,7,8]. HCV core was defined as a poor cellular immunogen, both when delivered as DNA and as a protein [9,10,11,12,13,14]. We have shown that plasmids directing higher levels of core expression were less immunogenic than directing lower levels of HCV core expression [5].…”
Section: Introductionmentioning
confidence: 99%